(untitled) (Marketing Journal, 2026)
The article provides an in -depth scientific analysis of the theoretical and practical aspects of tour operator activities, modern classification approaches, and their organizational and economic significance. It highlights the classification of mass - market and specialized types of tour operators, their market segments, the process of tour package formation, level of integration, service quality, and pricing policies. Additionally, the article comprehensively compares the interaction mechanisms between initi ative and receptive tour operators in the international tourism system, as well as the differences between tour operators and travel agents. The study also evaluates informational tourist trips, marketing strategies, digital transformation, № 1 -SON YANVA R, 202 6-YIL 195 sustainable development, and innovative technologies as modern trends in tour operator activities.